2021
DOI: 10.31486/toj.20.0004
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse-Driven Protocol for Foley Catheter Utilization Decreases the Incidence of Traumatic Foley Catheterization

Abstract: Background: Traumatic urethral catheterization is a common reason for urologic consultation in hospitalized patients. The purpose of this study was to determine if a protocol designed to decrease Foley catheter use was effective and if implementation of the protocol decreased the incidence of Foley catheter-associated trauma. Methods: In an effort to decrease catheter use, our institution adopted a nurse-driven Foley catheter protocol in May 2015 that allowed nurses to remove Foley catheters that did not meet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…We have not found any theory-driven intervention similar to ours to reduce bladder distension or UR. Most nurse-driven protocols have been shown to reduce both the length and use of IDC, associated UTIs and catheter trauma, by using appropriate indications, removal plans and timely bladder scanning [33,[59][60][61][62]. We found that more patients received a catheter over the intervention years and in parallel a decrease he incidence of UC-UTI [27].…”
Section: The Interventionmentioning
confidence: 72%
“…We have not found any theory-driven intervention similar to ours to reduce bladder distension or UR. Most nurse-driven protocols have been shown to reduce both the length and use of IDC, associated UTIs and catheter trauma, by using appropriate indications, removal plans and timely bladder scanning [33,[59][60][61][62]. We found that more patients received a catheter over the intervention years and in parallel a decrease he incidence of UC-UTI [27].…”
Section: The Interventionmentioning
confidence: 72%
“…En este sentido, lo anterior pone en evidencia la necesidad de que las enfermeras sean quienes deban velar por el adecuado cumplimiento de los protocolos en lo que se refiere a la seguridad y calidad de la atención en salud, por lo que es importante que los profesionales de enfermería se involucren en la gestión de los procesos, con la finalidad de que los cuidados asociados a la instalación y manejo de catéteres vesicales sean basados en la mejor evidencia disponible (5,(26)(27)(28) .…”
Section: Discussionunclassified
“…[8][9][10][11] Substantial outpatient management costs can also be incurred in addressing follow-up of long-term complications. 7,12,13 Limited efforts to minimize UC trauma have been reported with mixed results, 6,[14][15][16][17][18] and thus comprehensive research is needed to better understand the characteristics of such injuries. Knowledge gaps include the patient population characteristics that might be used to better identify an at-risk population suitable for earlier urologic intervention as well as the circumstances contributing to iatrogenic UC injury.…”
mentioning
confidence: 99%